PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL PADA MATERI KEANEKARAGAMAN HAYATI - gladys, salsabila; Fitri, Rahmadhani (Universitas Cokroaminoto Palopo, 2024)
The development of E-Modules for biology learning needs to be carried out so that the biology learning process can run more optimally. This research aims to test the feasibility of developing e-modules on biodiversity material as a learning medium. The type of research is development research using ADDIE Models. The research instruments were teacher interview guide sheets, student questionnaires, validity test questionnaires, and practicality test questionnaires. The e-module was validated by two lecturers from the Biology Department, FMIPA UNP and one biology teacher at SMAN 8 Padang. The e-module was tested on 2 biology teachers and 30 students of SMAN 8 Padang class X MIPA for the 2024/2025 academic year to test the practicality of the product being developed. The object of this research is an e-module on biodiversity material for class X SMA students. The data used in this research is primary data which is then analyzed qualitatively and quantitatively. Based on the research that has been carried out, the average validation result value is 93% (very valid). The practicality test carried out on teachers obtained a result of 92% (very practical) and the practicality test carried out on students obtained a result of 91% (very practical). So, it can be concluded that the e-module on biodiversity material for class X SMA students that was developed is valid and very practical.